Digital literacy, environment, and independence: a triad affecting students' academic achievement - Sulastri Aprilia; Sudi Dul Aji; Roni Alim Ba'diyah Kusufa (University of Muhammadiyah Malang, 2026)
The rapid development of digital technology requires elementary school students to possess adequate digital literacy skills to access, comprehend, and utilize information effectively in the learning process. However, observations in several elementary schools in Pasean District revealed that many students still struggle to use technology optimally, accompanied by low learning independence and insufficiently supportive learning environments. Based on these issues, this study aims to analyze the influence of digital literacy, learning environment, and learning independence on students’ science and social studies (IPAS) learning outcomes in grade V at elementary schools in Pasean District, Pamekasan Regency. This research employed a quantitative approach with a causal associative method. A total of 140 students were selected using purposive sampling. Data were collected through valid and reliable questionnaires and analyzed using multiple linear regression with SPSS 22. The results showed that digital literacy, learning environment, and learning independence simultaneously had a significant effect on students’ learning outcomes (R² = 0.864). Partially, each variable also had a significant effect with significance values of 0.023 for digital literacy, 0.003 for learning environment, and 0.000 for learning independence. These findings highlight the importance of strengthening digital literacy, creating a supportive learning environment, and fostering students’ learning independence to improve IPAS learning outcomes in elementary schools.